2014
DOI: 10.1080/02755947.2014.901261
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mini‐Fyke Nets for Sampling Shallow‐Water Fish Communities in Florida Lakes

Abstract: We evaluated mini‐fyke nets for sampling shore‐based (SB; <1 m deep) fish communities in Florida lakes. Specifically, we wanted to determine the most effective deployment method and sample size required for adequately characterizing fish communities in these habitats. Shallow SB (0.15–0.6 m) net sets, in which nets were not completely submersed, collected significantly more individuals and a larger proportion of poeciliids. However, deep SB (0.6–1.0 m) net sets, in which nets were completely submersed, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In most instances, littoral habitats in Lake Michigan are all deeper than 1.5 m and dominated by sandy or rocky substrate, and because nets are set in tandem most mini-fyke net sets are relatively deep for this gear. Bonvechio et al (2014a) found that even a subtle difference in set depth of 0.4 m could have appreciable differences in CPUE and diversity for this gear, and we suspect similar influences for our study areas.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…In most instances, littoral habitats in Lake Michigan are all deeper than 1.5 m and dominated by sandy or rocky substrate, and because nets are set in tandem most mini-fyke net sets are relatively deep for this gear. Bonvechio et al (2014a) found that even a subtle difference in set depth of 0.4 m could have appreciable differences in CPUE and diversity for this gear, and we suspect similar influences for our study areas.…”
mentioning
confidence: 48%
“…Mini-fyke nets are most often used to sample lentic fish communities in shallow (<1-m) waters (Bonvechio et al 2014a). Smaller meshes and openings prohibit entry to most larger-bodied species while selecting for more active species or those associated with cover, including centrarchids and cyprinids (Fago 1998;Clark et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We sampled fishes at each habitat on consecutive days using two techniques, fyke nets and trotlines. These methods were chosen because they are passive approaches minimally destructive to SAV; they were meant to target different fish sizes, species, and trophic levels; and they have been shown to be effective in freshwater fish sampling (Diana et al, 2006;Hubert et al, 2012;Bonvechio et al, 2014). Each fyke net was made up of two rectangular conduit 0.9 × 1.2 m frames, five 63.5 cm galvanized hoops, two throats, a 15.24 m long lead, and 0.6 cm mesh size with a black net coat treatment.…”
Section: Field Samplingmentioning
confidence: 99%
“…Although electrofishing is the most commonly used method in the routine monitoring of fish assemblages in the littoral zone of lakes (Minns et al, 1994;Pierce et al, 2001;CEN, 2003;Eggleton et al, 2010), several studies emphasise the use of complementary sampling methods for a more complete estimation of fish assemblage structure (e.g. Weaver & Magnuson, 1993;Clark et al, 2007;Bonvechio et al, 2014;Hinlo et al, 2017). Unlike other gears, fyke nets may be universally applicable for monitoring fish communities in a wide variety of littoral meso-habitats.…”
Section: Introductionmentioning
confidence: 99%